Smart grids and cyber security - Daş, Resul; Gündüz, Muhammed Zekeriya (Elsevier, 2024)
Developing communication technologies make systems more efficient. Especially the concept of the Internet of Things makes this efficiency even more effective. Power systems are evolving in terms of digitalization, and this evolution is called the smart grid in electrical systems. However, due to its nature, digitalization causes vulnerabilities in terms of cyber security. These vulnerabilities stand out as issues that are increasing and waiting to be resolved. Ensuring the basic objectives and requirements of cyber security is inevitable for the widespread use of smart grids. This is clearly seen when cyberattacks on power systems globally are examined. Integrating renewable energy sources into these systems can provide benefits in terms of cyber security in various aspects. In addition, the characteristics of assets in a smart grid system require their own tailor-made security. Applying up-to-date cyber security developments in smart grid networks is a necessity in terms of reliability. In this context, this chapter explores the significance of cyber security in smart grids, the potential threats, and the reliability that arises due to increased connectivity. It also examines the latest developments regarding cyber security in smart grids, focusing on key areas. © 2025 Elsevier Inc. All rights reserved.
Keywords: Cyber security; Cyberattacks; Smart grid